Shupihui: Bilingüismo y educación bilingüe en las minorías indígenas amazónicas: fracasos y expectativas - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1984)
Volumen IX, Número 30, abril-junio 1984; Bilingüismo y educación bilingüe en las minorías indígenas amazónicas: fracasos y expectativas

Shupihui: Volume IX, Number 30, April-June 1984 Bilingualism and bilingual education in Amazonian indigenous minorities: failures and expectations.
Shupihui: Bilingualism and bilingual education in Amazonian indigenous minorities: failures and expectations.
Keywords: Iquitos (Peru)--periodicals Peru--general periodicals Peru--periodicals Iquitos (Perú)--revistas Perú--revistas generales Perú--revistas